APPLICATION OF AREOLA AND ROLLING MASSAGE USING JITU OIL WITH AL-QURAN MUROTTAL RELAXATION ON SUCCESSFUL BREASTFEEDING - Ningsih, Dewi Andariya (Universitas Aisyah Pringsewu, 2024)
Breastfeeding is a mother's effort to provide the best nutrition for her baby. Even if a mother intends to breastfeed, successful breastfeeding is not always achieved because many factors influence it. Rolling and Areoal massage is one of the efforts to ensure the smooth flow of breast milk combined with Jitu Oil and relaxation of Al-Qur'an Murottal. Sixty-four samples of breastfeeding mothers with instrument measurements using the Person Product Moment Validity Test. Data were analyzed using the Kolmogorov-Smirnov Normality and the Chi-Square test. Independent Successful Breastfeeding between the pre-test and post-test was significantly different; all respondents experienced an increase in Independent Successful Breastfeeding. So, applying Areola and Rolling massage using Jitu Oil with Al-Qur'an Murottal relaxation significantly affects successful breastfeeding independently.